Revealing the Influences of Exogenous Chitosan Supplements on Yield, Nutritional Values and Enzyme Activities in Taşköprü Garlic - Turfan, Nezahat; Çiçek Aksoy, Asuman (Yuzuncu Yil Universitesi Tarim Bilimleri Dergisi, 2024)
Garlic (Allium sativum L.) Taşköprü garlic is a valuable source of antioxidative molecules, including phenolic compounds, flavonoids, phenolic acids, enzymes, and minerals. A two-year study was conducted in an open field to compare the potential influence of exogenous chitosan (CHT) supplements on garlic yield, ash content, secondary metabolite generations, antioxidant enzyme activity, and mineral status of Taşköprü garlic in comparison to the untreated groups. The applications were arranged as control (0), CHT (CHT-1:0.5 Mm, CHT-2: 1 mM, and CHT-3:2 mM), and NPK. The influences of the applications were measured by monitoring bulb and plot yield, total phenolic, flavonoid, phenolic acids, ascorbate peroxidase (APX), catalase (CAT), peroxidase (POD), and superoxide dismutase (SOD) activity, and K, P, S, Ca, Mn, Fe, Ni, Cu, Zn, and Se accumulations. Results revealed that CHT-1 application improved bulb yield; benzoic acid and rosmarinic acid; Cl, K, Ca, and Se accumulation in garlic samples, but CHT-2 application increased total phenol content, POD and SOD enzyme activity, and the Mn, Fe, Ni, Cu, and Zn concentrations. The CHT-3 application enhanced the flavonoid generation in the garlic tissues. In summary, exogenous chitosan supply improved bulb growth by inducing flavonoids, total phenolics, benzoic acid, K, Na, Cl, and Ca accumulation and by activating POD and SOD. Moderate levels of chitosan (CHT-1 and CHT-2) could be offered to garlic cultivation, and data obtained can also provide potential knowledge about pre-harvest traits of garlic bulbs for further investigation.
Keywords: Hasat Sonrası Bahçecilik Teknolojileri (Taşımacılık ve Depolama dahil); Ecology (Other); Post Harvest Horticultural Technologies (Incl. Transportation and Storage); Ekoloji (Diğer); Antioxidant; Chitosan; Enzyme; Garlic; Nutrition